Eponyms in the clinical anatomy of the human organ of vision - Svitlitsky, A. O.; Chernyavskiy, A. V.; Matvieishyna, T. M.; Shcherbakov, M. S.; Світлицький, Андрій Олександрович; Чернявський, Артур Валерійович; Матвєйшина, Тетяна Миколаївна; Щербаков, Максим Степанович (My University, 2022)
The purpose of this article was the analysis of modern international and Ukrainian sources with an attempt to systematize the names-eponyms of the structures of the visual analyzer, in particular the eyeball and its accessory visual structures.
Keywords: тези доповідей